Diseño de un modelo de políticas de seguridad informática para la universidad técnica de Cotopaxi. - Tulmo Checa, Darío Wladimir (2019)
Information and communication technologies (ICTs) have allowed for a highly digitized and globalized world. This makes individuals and organizations become increasingly dependent on technology and the Internet, therefore the risks and threats in their computer systems grow in large proportion. At the Technical University of Cotopaxi, there is a broad IT infrastructure that provides access to computer services that must comply with good practice guidelines for their availability. For this reason, the present research project aims to design a model of computer security policies for the University, which handles information of vital importance and needs to have security mechanisms that provide sufficient support to protect institutional information. The design of a computer security policy model will minimize risks and threats that could compromise the correct functioning of computing resources such as information, processes, systems and networks. To better support the research work, different computer security guidelines established and suggested in the ISO / IEC 27001 Standard were used, which seeks the confidentiality, integrity and availability of the information.